Single rotation-gated CT to demonstrate the inferior pulmonary ligaments and the sino-atrial node artery anatomy. (September 2015) - Geach, Rebecca; Khan, Jawad; Banister, Tom; Haslam, Elizabeth; McGann, Garrett
Abstract : Purpose: The inferior pulmonary ligaments (IPLs) and sino-atrial node artery (SANA) are thoracic structures difficult to image. Little has been published concerning frequency, size, origin and direction. The SANA course, origin and distribution are important, with increased frequency of trans-atrial septal intervention. The IPL may be important in lung collapse, consolidation, fluid collections and torsion. Methods and materials: The study included 100 consecutive cases of cardiac computed tomography (CT). For SANA, the vessel of origin and unusual anomalies were recorded. For left IPL (LIPL), length of the double pleural layer and presence/length rarer right IPL was documented. Anomalies and unusual shapes were recorded and whether the ligaments reached the hilum. Results: The SANA visualised 99 subjects: 66 from the right coronary artery 22 circumflex 9 patients dual supplies, right coronary artery (RCA) and circumflex. 2 exclusive supply branch directly from the aorta. Eleven patients origin at the distal circumflex. IPL seen 88% cases: 31 both left and right IPLs. 1 had only a right-sided ligament. Average corrected length LIPL: 55.1 millimetres (mm), right IPL (RIPL): 14.6 mm. Fourteen LIPLs traceable to the hilum. Previous CT studies suggested a double structure, this gated study showed no cases where the structure was visualised as two layers. Conclusion: We have documented the in-depth features on high-resolution Electrocardiogram (ECG) gated scanning using a unique single-rotation system acquiring 160 mm of x-axis data in 1/3 second. We believe changes documented in our study are due to the ultra-high resolution technique.